ANALYSIS OF MUSCULOSCKELETAL COMPLAINTS DISORDERED WITH REBA METHOD AND RULA METHOD : (CASE STUDY OF SMK BRANTAS KARANGKATES MALANG DISTRICT) - Wargiono, Didik; Hutabarat, Julianus; Laksmana, Dimas Indra (Journal of Sustainable Technology and Applied Science (JSTAS), 2021)
Class furniture, namely tables and chairs, are significant physical facilities because the furniture is used for teaching and learning activities. Pain in the neck, waist, right upper arm, right forearm and right wrist during the learning process due to non-ergonomic facilities. Therefore, this research aims to minimize the complaints of Musculoskeletal Disorder with the Ergonomic Learning Chair. In this study, descriptive research with the REBA method and the RULA method was used. With the REBA method, the final score obtained in Group C is 8, then this value is entered at Action Level 3, after which researchers can only find out that the student's body posture level is in the High category so that action is needed immediately. With the RULA method, the student's body activity results are at a Group C score of 7. The value is entered for Action Level 4 so that the student's posture is in the dangerous category for safety, health and comfort. Therefore, action is needed now to overcome this problem with the suggestion manufacture of Ergonomic Study Chair. From the results of the chair use test design analysis by distributing questionnaires to 35 students as a sample, it was found that there was a decrease in complaints of Musculoskeletal Disorder in the student body. With the contribution of the study table, it can be adjusted up and down (adjustable) to make the chair more comfortable.